Influence of apixaban on commonly used coagulation assays: results from the Belgian national External Quality Assessment Scheme. (17th March 2017) - Van Blerk, M.; Bailleul, E.; Chatelain, B.; Demulder, A.; Devreese, K.; Douxfils, J.; Jacquemin, M.; Jochmans, K.; Mullier, F.; Wijns, W.; China, B.; Vernelen, K.; et al.
Summary: Introduction: The Belgian national External Quality Assessment Scheme performed a survey to assess the effect of the direct oral anticoagulant apixaban on the coagulation assays prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen and antithrombin as performed with a large number of reagent/instrument combinations. Methods: Four lyophilized plasma samples spiked with apixaban (0, 41, 94 and 225 ng/mL) were sent to the 195 Belgian and Luxembourg clinical laboratories performing coagulation testing. Results: PT and aPTT were barely influenced at the concentrations tested. At 225 ng/mL apixaban, PT and aPTT clotting times were only 1.15 times longer than at 0 ng/mL. Among PT reagents, RecombiPlasTin 2G ® showed a slightly higher sensitivity with 225 ng/mL apixaban prolonging the PT clotting time 1.3‐fold. Among aPTT reagents, there was no appreciable difference in sensitivity. Fibrinogen results were unaffected by the presence of apixaban, but antithrombin activity was considerably overestimated when measured with a FXa‐based assay. At 225 ng/mL apixaban, the median percentage increase in antithrombin level was 31% when measured with the Liquid Antithrombin ® reagent and 44% with the Innovance Antithrombin ® reagent. Conclusion: Our data provide clinical laboratories with useful information on the impact of apixaban on their routine coagulation assays.